2019
DOI: 10.1093/gerona/glz041
|View full text |Cite
|
Sign up to set email alerts
|

Three Doses of Vitamin D and Cognitive Outcomes in Older Women: A Double-Blind Randomized Controlled Trial

Abstract: Vitamin D may affect cognitive performance, but previous studies are either short term or observational. We conducted a randomized controlled trial of vitamin D supplementation on domain-specific cognitive measures in postmenopausal women. Overweight/obese women with serum 25-hydroxyvitamin D (25OHD) levels less than 30 ng/mL were recruited. Vitamin D3 supplementation (600, 2,000, or 4,000 IU/d) was randomly assigned in a double-blinded manner for 1 year. Serum 25-hydroxyvitamin D, osteocalcin (total and under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 51 publications
0
36
0
2
Order By: Relevance
“…Unfortunately, current published intervention trials addressing vitamin D and cognition have not provided a conclusive answer (Dhesi et al, 2004; Przybelski et al, 2008; Dean et al, 2011; Stein et al, 2011; Rossom et al, 2012; Pettersen, 2017; Rutjes et al, 2018; SanMartin et al, 2018; Castle et al, 2019). A recent small intervention trial showed general cognitive status improvement in 16 mild cognitive impaired patients after 18 months of vitamin D supplementation (but not in healthy controls or those already diagnosed with dementia; SanMartin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, current published intervention trials addressing vitamin D and cognition have not provided a conclusive answer (Dhesi et al, 2004; Przybelski et al, 2008; Dean et al, 2011; Stein et al, 2011; Rossom et al, 2012; Pettersen, 2017; Rutjes et al, 2018; SanMartin et al, 2018; Castle et al, 2019). A recent small intervention trial showed general cognitive status improvement in 16 mild cognitive impaired patients after 18 months of vitamin D supplementation (but not in healthy controls or those already diagnosed with dementia; SanMartin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Improved visual memory was observed in healthy Canadian adults with “insufficient” baseline 25(OH)D levels (below 75 nmol/l) that were supplemented with high doses of vitamin D (4,000 IU per day) for 18 weeks, without replication in other cognitive domains (Pettersen, 2017). More recently, in a randomized controlled trial with 69 overweight/obese postmenopausal women with 25(OH)D levels less than 75 nmol/l and divided in three different intervention doses of vitamin D (600, 2,000 or 4,000 IU per day), only the intermediate group performed better in learning and memory tests after 1 year supplementation (Castle et al, 2019). These results reflect the complexity behind any potential vitamin D effect on cognition and the need for better-designed studies, probably including distinct vitamin D insufficiency status populations, supplement doses, exposures periods, age groups and baseline cognitive performances.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits are indicated on global cognitive performance (79) and in specific cognitive domains including visuospatial skills, language, working memory, memory recall, concentration and attention (80) . However, other studies indicate that exaggerated levels of vit-D are also associated with poorer cognitive function (25,(81)(82)(83) . Moreover, adding to the complexity of interpretating vit-D-associated CNS effects is the significant potential confounder of reverse causation and in lack of standardisation and heterogeneity of blood vit-D analytics (82,84) .…”
Section: Vitamin D and Cognitive Performancementioning
confidence: 99%
“…A study by Rossom et al (92) failed to demonstrate positive effects of vit-D supplementation in attenuating cognitive dysfunction, or on lowering the risk of dementia when compared with placebo. Moreover, Castle and colleagues recently reported on the differential dosage effects of vit-D on specific cognitive domains in healthy, post-menopausal women whereby higher doses were found associated with poorer reaction time and measures of learning and memory (83) . Furthermore, a recent literature review by Landel et al (72) determined that there was no solid evidence to suggest that exogenous supplementation of vit-D improves cognition in those who already have sufficient serum levels of vit-D.…”
Section: Hypovitaminosis D and Cognitive Performancementioning
confidence: 99%
“…A recent cohort in Boston-area Puerto Ricans showed that the association of serum 25(OH)D concentration with individual cognitive test scores was not statistically significant [ 19 ]. However, another recent study in women suggested that higher 25(OH)D concentrations might have negative cognitive effects [ 20 ]. Additionally, currently, no study investigated the dose–response relationships between them.…”
Section: Introductionmentioning
confidence: 99%